2012
DOI: 10.1016/j.bbamem.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of membrane tension on the physical properties of DOPC lipid bilayer membrane

Abstract: Molecular dynamics simulations of a dioleoylphosphocholine (DOPC) lipid bilayer were performed to explore its mechanosensitivity. Variations in the bilayer properties, such as area per lipid, volume, thickness, hydration depth (HD), hydration thickness (HT), lateral diffusion coefficient, and changes in lipid structural order were computed in the membrane tension range 0 to 15 dyn/cm. We determined that an increase in membrane tension results in a decrease in the bilayer thickness and HD of ∼5% and ∼5.7% respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 96 publications
(132 reference statements)
19
77
0
Order By: Relevance
“…1. The resulting area expansion coefficients for DPhPC (K A = 222 ± 14 mN/m; mean ± SD for n = 8 ramps from two GUVs) and DOPC (K A = 199 ± 48 mN/m; mean ± SD for n = 6 ramps from two GUVs) are comparable to the area expansion coefficients measured by micropipette aspiration (265 ± 18 mN/m for DOPC) (37), and in excellent agreement with the reported area and thickness changes from molecular dynamics simulations (effective K A = 220 mN/m for DOPC) (38). Thus, the whole-GUV method allows membrane tension to be varied from the lowest physiologically relevant levels right up to the lysis tension of the membrane while simultaneously controlling the membrane voltage and measuring the membrane current, which has allowed us to confirm the predicted relationship between membrane capacitance and tension directly (Eq.…”
Section: Resultssupporting
confidence: 73%
“…1. The resulting area expansion coefficients for DPhPC (K A = 222 ± 14 mN/m; mean ± SD for n = 8 ramps from two GUVs) and DOPC (K A = 199 ± 48 mN/m; mean ± SD for n = 6 ramps from two GUVs) are comparable to the area expansion coefficients measured by micropipette aspiration (265 ± 18 mN/m for DOPC) (37), and in excellent agreement with the reported area and thickness changes from molecular dynamics simulations (effective K A = 220 mN/m for DOPC) (38). Thus, the whole-GUV method allows membrane tension to be varied from the lowest physiologically relevant levels right up to the lysis tension of the membrane while simultaneously controlling the membrane voltage and measuring the membrane current, which has allowed us to confirm the predicted relationship between membrane capacitance and tension directly (Eq.…”
Section: Resultssupporting
confidence: 73%
“…Under the above concentration conditions, Dr eq /r 0 for GUVs with a radius of 10 mm is 6.2 Â 10 À3 , which is 13 times larger than that for LUVs with a radius of 100 nm (¼ 4.9 Â 10 À4 ), and hence, s eq osm for the GUV is 13 times larger than s eq osm for the LUV. To validate this theory on the radius dependence of s eq osm , we measured a change in a physical property of lipid membranes induced by P. It was recently reported that the membrane stretching due to lateral tension increases the fluidity of lipid membranes (45,46) and the diffusion coefficient of lipid molecules (45)(46)(47). To monitor the fluidity of the membranes, we used generalized emission polarization value (GP) of Laurdan in membranes, because it is generally considered that with an increase in fluidity of lipid membranes the interaction of water molecules with a Laurdan molecule in the membrane interface increases, which causes the GP value to decrease (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…DOPC-GUVs were prepared by natural swelling in water (MilliQ) containing sucrose as follows (27). DOPC in chloroform (1.0 mM, 200 mL) in a small glass bottle (5 mL) was dried by N 2 gas to produce a thin, homogeneous lipid film; then, residual chloroform in the film was removed by placing the bottle in a vacuum desiccator connected to a rotary vacuum pump for >12 h. MilliQ water (20 mL) was added and the bottle was sealed and incubated in [45][46][47] C water for 8 min (prehydration). Then, 1.0 mL of 100.0 mM sucrose in MilliQ was added gently, and the bottle was resealed and incubated in an incubator at 37 C for 2 h to produce a GUV suspension.…”
Section: Methodsmentioning
confidence: 99%
“…From the response to osmotic pressure, the material constants are then evaluated for the membrane deformation. Such structural measures can also be used to experimentally validate molecular dynamics (MD) simulations [81, 82] of lipid systems and biomembranes [53, 54, 83]. The molecular force fields encapsulate the data obtained with different experimental techniques [84].…”
Section: Implications Of Membrane Deformation Due To Osmotic Stressmentioning
confidence: 99%